Mechanical Failure of the Distal Radius Volar Locking Plate. (December 2013) - Foo, Tun-Lin; Gan, Aaron WT; Soh, Tamara; Chew, Winston YC
Purpose: To review 9 cases of mechanical failure of the volar locking plate for distal radial fractures. Methods: Records of 374 consecutive patients who underwent volar locking plating for distal radial fractures were reviewed. Mechanical failures of the volar locking plate were defined as plate breakage or bending, screw breakage or loosening, or collapse of articular fragments resulting in intra-articular screw extrusion. Results: Nine mechanical failures occurred between 2 weeks and 3 months in 8 (2.4%) of the patients aged 25 to 82 (median, 74) years with AO fracture types of A3 (n=4), C1 (n=1), C2 (n=1), and C3 (n=3). Mechanical failures included screw pullout (n=5), locking plate bending (n=2), locking screws breakage (n=1), and loosening of locked variable angle screws (n=1). One patient underwent revision of fixation and 2 underwent implant removal. The remainder were treated conservatively. All patients were followed up for a minimum of 12 months; their mean flexion arc was 87° (standard deviation [SD], 17°) and the mean rotation arc was 136° (SD, 29°). According to the Green and O'Brien score, their outcomes were good (n=1), fair (n=4), and poor (n=3). Conclusion: Although mechanical failure of volar locking plate is uncommon, some are potentially preventable.